Oculomotor atypicalities in motor neurone disease: a systematic review - Readman, Megan Rose; Polden, Megan; Gibbs, Melissa C.; Donohue, Aisling; Chhetri, Suresh K.; Crawford, Trevor J. (Frontiers in Neuroscience, 2024)
Cognitive dysfunction is commonplace in Motor Neurone Disease (MND). However, due to the prominent motor symptoms in MND, assessing patients' cognitive function through traditional cognitive assessments, which oftentimes require motoric responses, may become increasingly challenging as the disease progresses. Oculomotor pathways are apparently resistant to pathological degeneration in MND. As such, abnormalities in oculomotor functions, largely driven by cognitive processes such as saccades and smooth pursuit eye movement, may be reflective of frontotemporal cognitive deficits in MND. Thus, saccadic and smooth pursuit eye movements may prove to be ideal mechanistic markers of cognitive function in MND. To ascertain the utility of saccadic and smooth pursuit eye movements as markers of cognitive function in MND, this review summarises the literature concerning saccadic and smooth pursuit eye movement task performance in people with MND. Of the 22 studies identified, noticeable patterns suggest that people with MND can be differentiated from controls based on antisaccade and smooth pursuit task performance, and thus the antisaccade task and smooth pursuit task may be potential candidates for markers of cognition in MND. However, further studies which ascertain the concordance between eye tracking measures and traditional measures of cognition are required before this assumption is extrapolated, and clinical recommendations are made.